Salivary Cortisol Levels in Athletes and Nonathletes: A Systematic Review - Cevada, T.; Vasques, P. E.; Moraes, H.; Deslandes, A. (Hormone and Metabolic Research, 2014)
High performance athletes are constantly facing different situations involving stress. Salivary cortisol has been used as a physiological measure to verify high performance athlete and mental health, in spite of research that has shown that comparisons between cortisol levels in athletes and nonathletes are inconclusive. The purpose of this study was to review articles that investigated salivary cortisol levels at rest in high performance athletes in comparison to physically active or sedentary nonathlete individuals. PubMed, ISI Web of Knowledge, SciELO, LILACS, and Scopus databases were searched for studies on salivary cortisol in athletes and the size effect was calculated. Although 3 articles reported higher salivary cortisol levels in female athletes compared to a control group, the results showed homogeneity among baseline groups or groups in resting conditions, suggesting a lack of discriminative capacity. These results should be interpreted with caution, due to the presence of substantial methodological bias.
Keywords: performance; sport psychology; stress; sport endocrinology